Soilless culture nutrient solution capable of improving yield of phaseolus vulgaris and preparation method of soilless culture nutrient solution - FU YU (2018)
The invention discloses a soilless culture nutrient solution capable of improving the yield of phaseolus vulgaris. The soilless culture nutrient solution is prepared from the following components in parts by weight: 0.5 to 1.5 parts of a macro-element, 0.002 to 0.01 part of a microelement, 0.05 to 0.5 part of an active substance and 500 to 2000 parts of de-ionized water. A preparation method of the soilless culture nutrient solution comprises the following steps: preparing the macro-element, the microelement and the active substance into a mother solution A, a mother solution B and a mixture Crespectively; mixing the mother solution A and the mother solution B according to the weight parts of the macro-element and the microelement; then adding the mixture C according to the weight ratio of the active substance; uniformly stirring to obtain the nutrient solution. The invention provides the nutrient solution for carrying out soilless culture on the phaseolus vulgaris and the requirements on various elements in